2020
DOI: 10.1097/ccm.0000000000004225
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Among Medicare Beneficiaries: 3. The Methods, Models, and Forecasts of Sepsis, 2012–2018*

Abstract: Objective: To evaluate the impact of sepsis, age, and comorbidities on death following an acute inpatient admission and to model and forecast inpatient and skilled nursing facility costs for Medicare beneficiaries during and subsequent to an acute inpatient sepsis admission. Design: Analysis of paid Medicare claims via the Centers for Medicare & Medicaid Services DataLink Project (CMS) and leveraging the CMS-Hierarchical Condition Category risk adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 10 publications
1
61
1
1
Order By: Relevance
“…In this report, we observe that stays with different severity tiers have differently improving survival over the study interval. Separating the study population into monthly cohorts (each monthly cohort contains 70,000 to >100,000 sepsis inpatient admissions) and further stratifying by severity, we observed that the survival data of the septic shock cohorts and of the nonsevere sepsis (either organism specified or organism unspecified) cohorts show modest improvements over the interval, a finding consistent with reports by others (1,14). In contrast, the data show a marked improvement in survival of the severe sepsis patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this report, we observe that stays with different severity tiers have differently improving survival over the study interval. Separating the study population into monthly cohorts (each monthly cohort contains 70,000 to >100,000 sepsis inpatient admissions) and further stratifying by severity, we observed that the survival data of the septic shock cohorts and of the nonsevere sepsis (either organism specified or organism unspecified) cohorts show modest improvements over the interval, a finding consistent with reports by others (1,14). In contrast, the data show a marked improvement in survival of the severe sepsis patients.…”
Section: Discussionsupporting
confidence: 88%
“…In the first article of this set, we discussed potential explanations for the rise in inpatient admissions assigned a sepsis code (1). In this report, we observe that stays with different severity tiers have differently improving survival over the study interval.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Post-sepsis syndrome has been increasingly recognized as a major contributor to poor longterm health after critical illness (19,25) which includes sequelae affecting physical, mental, and psychological health in all age groups, affecting long-term development of neonates and children with an impact lasting decades (4,37). In the United States, the inpatient admission and subsequent skilled nursing facility costs for sepsis in Medicare beneficiaries have risen up to 62 billion USD in 2018 (5). The full societal impact of sepsis due to reduced productivity of survivors, dependency on support in everyday life, and the multiplying effect on carers, siblings, and children has not been reliably assessed but is likely to exceed the direct sepsis costs several fold (27,28).…”
Section: Recent Insights Into the True Sepsis Burdenmentioning
confidence: 99%
“…This reaction leads to aberrant immune responses and if not diagnosed and treated early after its onset, may limit survival by inducing coagulopathy, altered microvasculature, and dysregulation of the host's metabolism and organ function [1][2][3][4][5][6][7] . Sepsis accounts for one in three hospital deaths in the U.S. and millions of deaths each year globally, highlighting its hazard to public health 8,9 . The high mortality rate associated with sepsis reflects the lack of a clinically viable molecular-based therapeutic target.…”
Section: Introductionmentioning
confidence: 99%